The double vulnerability of elderly caregivers: multimorbidity and perceived burden and their associations with frailty - Alves,Erika Valeska da Costa (2018)
Abstract Objective: To identify if multimorbidity and burden are associated with a greater likelihood of frailty in elderly caregivers of other elderly persons within the family context. Method: 148 elderly caregivers caring for other elderly persons [M=69.7 (±7.0) years old] were recruited using a criterion of convenience in public and private health services in the city of Campinas and surrounding areas. Information was gathered about socio-demographic context, context of care, physical health, care burden using the Zarit Burden Scale, and frailty, measured by subjective evaluation. Four groups of vulnerability were created based on the presence or absence of multimorbidities and high or low burden, in order to verify which group was most strongly associated with frailty. Data were analyzed using descriptive analysis, measurements of association and multivariate hierarchical logistic regression. Results: The prevalence of multimorbidity was 55.4%. The Zarit Burden Scale presented a median of 23 out of a total of 88 points. Of the sample, 35.1% were frail, 46.0% intermediate, and 18.9% robust. Elderly caregivers with multimorbidity and high burden had a greater probability of frailty (OR=3.6; CI 1.55-8.36), followed by those with multimorbidity and low burden (OR=2.8; CI 1.13-6.79). Conclusion: The sensation of burden among caregivers was reduced; those with double vulnerability were most prevalent among the four groups and had the greatest association with the occurrence of frailty; multimorbidity was associated with frailty. If combined with perceived burden, however, the odds ratios of the elderly caregivers being frail increased.